1998
DOI: 10.1017/s0308229600032281
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between meat quality or composition and animal performance in double muscled Belgian Blue bulls

Abstract: As far as consumers are concerned, the major quality characteristics of beef meat are an attracting color and tenderness (Smulders et al., 1991). The chemical composition - protein, fat and fatty acids contents mainly - is of importance for the dietitian. These parameters are influenced to a large extent by the management - diet and environment - of the fattening animals. The aim of the present paper is to relate some parameters of meat quality and meat composition with animal performance in growing fattening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similar findings were also reported by Hornick et al (1998) with bulls showing compensatory growth. Indeed, Minet et al (1998) showed recently that the duration of the fattening is one of the most important parameter for determination of meat tenderness in Belgian Blue bulls. Indeed, Minet et al (1998) showed recently that the duration of the fattening is one of the most important parameter for determination of meat tenderness in Belgian Blue bulls.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were also reported by Hornick et al (1998) with bulls showing compensatory growth. Indeed, Minet et al (1998) showed recently that the duration of the fattening is one of the most important parameter for determination of meat tenderness in Belgian Blue bulls. Indeed, Minet et al (1998) showed recently that the duration of the fattening is one of the most important parameter for determination of meat tenderness in Belgian Blue bulls.…”
Section: Discussionmentioning
confidence: 99%